Preparation method of sand washing mud-based pressed product and sand washing mud-based pressed product

By using ionic biomass polymer and microwave activation technology in sand washing mud to form a network structure, it solves the problem of low hardened body strength and high energy consumption in traditional sand washing solidifiers, and achieves high efficiency and environmental protection. Preparation of sand washing mud -based pressing products.

CN119330640APending Publication Date: 2025-01-21HEFEI CEMENT RESEARCH AND DESIGN INSTITUTE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411469848.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, when dealing with sand washing mud, the method of adding curing agent has the disadvantages of low harden strength, complex wet process and high energy consumption, which is difficult to meet the application requirements.

Method used

The coupling effect of ionic biomass polymers and sand washing mud is used to form a network structure through the steps of semi -dry dehydration and microwave activation, which significantly improves the mechanical properties of pressure products.

Benefits of technology

It improves the pressure resistance and molding speed of the pressure products, overcomes the problem of low intensity of traditional craftsmanship and high energy consumption, and realizes the efficient use of sand washing resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330640A_ABST
    Figure CN119330640A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sand washing mud-based pressed product, which comprises the following steps: carrying out semi-dry dehydration on sand washing mud until the water content is 15-20%, and then mixing the sand washing mud with biopolymer powder to obtain a premix, the biopolymer powder comprises cationic polymer powder and anionic polymer powder; loading the premix into a mold, and carrying out compression molding to obtain a pressed product mold blank; and activating the pressed product mold blank by using microwaves to obtain the sand washing mud-based pressed product. Therefore, the pressed product prepared by the preparation method disclosed by the invention has the advantages of high forming speed, high compressive strength and no need of a long-time autoclaved activation process, the forming period is greatly prolonged, and the large-scale yield is favorably increased. The raw materials are rich in source, solid waste resource utilization of the sand washing mud can be achieved, waste is turned into wealth, and the environmental burden is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of raw pressed product production, in particular to a method for preparing a washed sand mud-based pressed product. Background Art

[0002] With the vigorous development of industrialization and urbanization in my country, the demand for building materials such as sand and gravel has risen sharply. However, due to the gradual depletion of natural resources and the continuous construction of infrastructure, the contradiction between the supply and demand of natural sand has become increasingly acute. Therefore, due to the characteristics of abundant sources and controllable quality, artificial sand has quickly become a substitute for natural sand. Due to the limitations of raw material sources, crushing and production technology conditions, artificial sand will inevitably produce powder particles (stone powder and mud powder) during the production process, which will have a negative impact on the quality of concrete prepared by artificial sand. Therefore, in order to obtain high-quality artificial sand, sand and gravel enterprises need to clean the soil on the surface of the mined sand and gravel, as well as the stone powder and mud powder in the process of preparing artificial sand during the production process. The large amount of mud and water mixture produced in this way is collectively referred to as sand washing mud.

[0003] However, due to the characteristics of high water content, high clay content, and poor engineering properties, the disposal and resource utilization of sand washing mud are difficult and the methods are difficult to unify. At present, the traditional treatment methods of sand washing mud mainly include engineering backfill, low-lying landfill, mine backfill, etc. Although these methods are easy to operate and have a short treatment cycle, they mainly rely on the absorption capacity of downstream receiving points, cannot be recycled, and are not sustainable. Therefore, the recycling of sand washing mud resources has become a hot topic of research at home and abroad.

[0004] Using a curing agent to solidify the sand-washing mud and then use it to produce pressed building materials is one of the important ways to recycle the sand-washing mud. This pressed product can be widely used in road infrastructure construction, greening projects, underground landfills, flood control and revetment projects, environmental restoration projects, and decorative landscape projects. There are two traditional ways to add curing agents: wet and dry. The wet method is to dilute the sand-washing mud into a slurry by adding additional water, and then add the curing agent. Although this method is easy to evenly disperse the curing agent, the strength of the cured body after hardening is low and cannot meet the application requirements; the dry method is to dry and crush the sand-washing mud, and then add the curing agent. This method is complex and energy-intensive, which affects resource utilization. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a sand-washing mud-based pressed product, which utilizes the coupling effect of ionic biomass polymer and sand-washing mud to improve the mechanical properties of the pressed product.

[0006] According to a first aspect of an embodiment of the present invention, a method for preparing a washed sand mud-based pressed product comprises the following steps:

[0007] S1. Semi-dry dehydration of sand washing mud to a moisture content of 15% to 20%;

[0008] S2. Mixing the semi-dry washed sand mud with biopolymer powder to obtain a premix, wherein the biopolymer powder includes cationic polymer powder and anionic polymer powder, the washed sand mud accounts for 96% to 98% by weight, the biopolymer accounts for 2% to 4% by weight, the cationic polymer powder is any one of chitosan, cationic starch, cationic cellulose derivatives and polyquaternary ammonium salts, and the anionic polymer powder is any one of sodium alginate, anionic cellulose, collagen, pectin and gum arabic; the mass ratio of the cationic polymer to the anionic polymer is in the range of (80 to 90): (10 to 20).

[0009] S3, loading the premix into a mold and pressing it on a press at 10MPa-15MPa to obtain a mold base for a pressed product;

[0010] S4, after the mold base of the pressed product is activated by microwave, a washed sand mud-based pressed product is obtained, wherein the microwave activation includes preliminary microwave activation and deep microwave activation, the time range of the preliminary microwave activation is 45min-60min, the microwave frequency is 433MHz-915MHz, the time range of the deep microwave activation is 30min-45min, the microwave frequency is 245MHz-915MHz. The temperature range of the microwave activation is 50℃-80℃, and the power range of the microwave is 2kW-5kW.

[0011] Specifically, the ionic biopolymer curing agent used in the present invention not only has the effects of strengthening, modifying and bridging the sand washing mud, but also significantly improves the mechanical properties of the pressed products through double charge interaction, wherein the first charge interaction occurs between the polymer binder and the sand washing mud, mainly including adsorption, charge neutralization and flocculation, thereby enhancing the bonding performance of the interface; the second charge interaction occurs between biopolymers with opposite charges, and this interaction can further improve the strength of the polymer binder.

[0012] Furthermore, the present invention utilizes a microwave source of a specific frequency (245MHz to 915MHz) with excellent penetrability, which not only realizes the synchronous heating of the inside and outside of the pressed product, making the temperature of each part of the block uniform and avoiding stress damage caused by temperature difference, but also effectively promotes the dissolution of water in the polymer powder and the sand washing mud.

[0013] Under the action of microwaves, the long molecular chains of biopolymers are unfolded, surrounding and covering the soil particles. As the water gradually evaporates, these polymer chains form a network structure between the sand washing mud particles, further enhancing the mechanical properties of the pressed products through the "bending mechanism" and "interweaving mechanism".

[0014] It should be noted here that due to the influence of factors such as charge shielding effect, pH sensitivity, high ionic strength, high molecular weight of polymer and temperature change, the polymer chains of ionic biopolymers are easily attracted and entangled with each other to form precipitates or gels, which limits their uniform dispersion in the solution. Therefore, directly preparing the ionic biopolymer solution and mixing it with sand washing mud may lead to problems of low dosage and poor dispersion of the polymer.

[0015] Therefore, in the present invention, the washed sand mud is first semi-dry treated and then mixed with the powdered ionic biopolymer, which facilitates more uniform mixing between the polymer and the washed sand mud and is conducive to forming a more uniform network structure during microwave activation, thereby improving the mechanical properties of the pressed product.

[0016] At the same time, after the sand washing mud is dehydrated to semi-dryness, the present invention exhibits powdery characteristics to a certain extent and retains some moisture, which can ensure uniform mixing with the biopolymer powder and make the biopolymer more dispersible, and can fully utilize the moisture retained in the sand washing mud during activation, thereby avoiding the repeated process of dehydrating first and then adding water, and effectively overcoming the shortcomings of low intensity of wet process, complex dry process and high energy consumption.

[0017] A pressed product according to the second aspect of the embodiment of the present invention is a pressed product prepared by any of the above-mentioned preparation methods. The pressed product has excellent mechanical properties and durability, and is conducive to being widely used in multiple fields such as road infrastructure construction, greening projects, underground landfills, flood control and bank protection projects, environmental restoration projects, and decorative landscape projects. At the same time, it can promote the recycling of sand washing mud solid waste resources.

[0018] Beneficial effects:

[0019] The pressed product prepared by the preparation method of the present invention has a fast forming speed and high compressive strength, does not require a long autoclave activation process, greatly improves the forming cycle, and is conducive to increasing large-scale production. In addition, the raw material source is abundant, and the solid waste resource utilization of sand washing mud can be realized, turning waste into treasure and reducing the environmental burden.

[0020] In the present invention, biopolymer is used as a bonding and curing agent, the components of the pressed product are simpler, and the cement component is omitted, which is more energy-saving and environmentally friendly, and avoids the problem of large amounts of energy consumed and large amounts of carbon emissions generated during the production of cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 Schematic diagram of biopolymer charge interactions according to an embodiment of the present invention. DETAILED DESCRIPTION

[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present disclosure in conjunction with the drawings in the embodiments disclosed in this application. The description of the embodiments is actually only illustrative and exemplary, and does not serve as any limitation to the present disclosure and its application or use; based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without carrying out creative work should fall within the scope of protection of the present disclosure. In addition, the technologies, methods and equipment known to ordinary technicians in the relevant fields may not be discussed in detail, but where appropriate, the technologies, methods and equipment should be regarded as part of the specification.

[0024] Example 1

[0025] In this embodiment, the washed sand mud-based pressed product is prepared according to the following steps:

[0026] First, dehydrate the sand washing mud to a moisture content of 15%, then quickly stir 98% of the sand washing mud and 2% of the biopolymer powder (the mass ratio of the cationic polymer polyquaternary ammonium salt-chitosan and the anionic polymer collagen is 80:20) for 2 minutes until the mixture is uniform, take out the material and put it into the mold, and form it on a press, and the molding pressure is 15MPa.

[0027] After the specimen is demolded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 45 minutes and the microwave frequency is 433 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 45 minutes and the microwave frequency is 433 MHz. The temperature is controlled at 50°C and the power is 5 kW. After the curing is completed, the pressed product can be obtained.

[0028] Example 2

[0029] In this embodiment, the washed sand mud-based pressed product is prepared according to the following steps:

[0030] First, dehydrate the sand washing mud to a moisture content of 20%, and then quickly stir 96% of the sand washing mud and 4% of the biopolymer powder (the mass ratio of the cationic polymer etherified starch to the anionic polymer sodium alginate is 90:10) for 2 minutes until the mixture is uniform. Then, take out the material and put it into the mold, and form it on a press. The forming pressure is 10MPa.

[0031] After the specimen is demoulded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 60 minutes and the microwave frequency is 915 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 30 minutes and the microwave frequency is 433 MHz. The temperature is controlled at 80°C and the power is 2 kW. After the curing is completed, the pressed product can be obtained.

[0032] Example 3

[0033] In this embodiment, the washed sand mud-based pressed product is prepared according to the following steps:

[0034] First, dehydrate the sand washing mud to a moisture content of 18%, then quickly stir 97% of the sand washing mud and 3% of the biopolymer powder (the mass ratio of cationic polymer etherified starch to anionic polymer polyanionic cellulose is 85:15) for 2 minutes until the mixture is uniform, take out the material and put it into a mold, and form it on a press, and the molding pressure is 13MPa.

[0035] After the specimen is demolded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 55 minutes and the microwave frequency is 650 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 38 minutes and the microwave frequency is 350 MHz. The temperature is controlled at 65°C and the power is 4 kW. After the curing is completed, the pressed product can be obtained.

[0036] Comparative Example 1:

[0037] Comparative Example 1 is the control group of Example 2. The water content of the sand washing mud in the steps of Example 2 is changed from 20% to 40%, and the molding method is changed to casting molding. The specific method steps are as follows:

[0038] First, the washed sand mud is dehydrated to a moisture content of 40%, and 96% of the washed sand mud and 4% of the biopolymer powder (the mass ratio of the cationic polymer etherified starch to the anionic polymer sodium alginate is 90:10) are quickly stirred for 2 minutes until the mixture is evenly mixed. The materials are taken out and loaded into the mold and allowed to stand until they can be demolded. After the test piece is demolded, the mold is transferred to the microwave reaction chamber. First, preliminary microwave curing is carried out. The preliminary microwave curing time of the pressed product is 60 minutes, and the microwave frequency is 915MHz. After the preliminary microwave curing is completed, deep microwave curing is carried out. The deep microwave curing time is 30 minutes, the microwave frequency is 433MHz, the temperature is controlled at 80℃, and the power is 2kW. After the curing is completed, the cast molded parts can be obtained.

[0039] Comparative Example 2:

[0040] Comparative Example 1 is the control group of Example 2, and the water content of the sand washing mud in the steps of Example 2 is changed from 20% to 0%. The specific method steps are as follows:

[0041] First, dehydrate the sand washing mud to a moisture content of 0%, and then grind the dried sand washing mud. Quickly stir 96% of the sand washing mud and 4% of the biopolymer powder (the mass ratio of the cationic polymer etherified starch to the anionic polymer sodium alginate is 90:10) for 2 minutes until the mixture is uniform. Then, add water at a uniform speed, the amount of water added is 20% of the sand washing mud, stir again for 2 minutes until the materials are uniformly stirred, take out the materials and put them into the mold, and form them on the press. The forming pressure is 10MPa.

[0042] After the specimen is demoulded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 60 minutes and the microwave frequency is 915 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 30 minutes and the microwave frequency is 433 MHz. The temperature is controlled at 80°C and the power is 2 kW. After the curing is completed, the pressed product can be obtained.

[0043] Comparative Example 3:

[0044] Comparative Example 1 is the control group of Example 2, in which the anionic polymer sodium alginate in the steps of Example 2 is replaced by the cationic polymer etherified starch, and the remaining method steps remain the same as those of Example 2, namely:

[0045] First, dehydrate the sand washing mud to a moisture content of 20%, and quickly stir 96% of the sand washing mud and 4% of the biopolymer powder (of which cationic polymer etherified starch accounts for 100%) for 2 minutes until the mixture is uniform. Take out the material and put it into the mold, and form it on a press. The molding pressure is 10MPa.

[0046] After the specimen is demoulded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 60 minutes and the microwave frequency is 915 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 30 minutes and the microwave frequency is 433 MHz. The temperature is controlled at 80°C and the power is 2 kW. After the curing is completed, the pressed product can be obtained.

[0047] Comparative Example 4:

[0048] Comparative Example 1 is the control group of Example 2, in which the cationic polymer etherified starch in the steps of Example 2 is replaced with anionic polymer sodium alginate, and the remaining method steps remain the same as those of Example 2, namely:

[0049] First, dehydrate the sand washing mud to a moisture content of 20%, and quickly stir 96% of the sand washing mud and 4% of the biopolymer powder (of which the anionic polymer sodium alginate accounts for 100%) for 2 minutes until the mixture is uniform. Take out the material and put it into the mold, and form it on a press. The molding pressure is 10MPa.

[0050] After the specimen is demoulded, the brick is transferred to the microwave reaction chamber and first subjected to preliminary microwave curing. The time for preliminary microwave curing of the pressed product is 60 minutes and the microwave frequency is 915 MHz. After the preliminary microwave curing of the pressed product, deep microwave curing is carried out. The time for deep microwave curing of the pressed product is 30 minutes and the microwave frequency is 433 MHz. The temperature is controlled at 80°C and the power is 2 kW. After the curing is completed, the pressed product can be obtained.

[0051] Comparative Example 5:

[0052] Comparative Example 1 is the control group of Example 2, except that the microwave curing in the steps of Example 2 is replaced by steam curing, and the remaining method steps are the same as those of Example 2, namely:

[0053] First, dehydrate the washed sand mud to a moisture content of 20%, then quickly stir 96% of the washed sand mud and 4% of the biopolymer powder (of which the anionic polymer sodium alginate accounts for 100%) for 2 minutes until the mixture is evenly mixed, take out the material and put it into a mold, and form it on a press with a molding pressure of 10 MPa. After the test piece is demolded, transfer the brick to a steam curing box with the temperature controlled at 80°C and run for 90 minutes. After curing, the pressed product can be obtained.

[0054] Test example:

[0055] 1. Compressive strength

[0056] The compressive strength is measured according to GB / T 5348 standard. After the activation of the specimen is completed, it is tested using a 300kN constant stress pressure testing machine. The test loading speed is 2.4kN / s. During the test, the specimen is precisely placed in the center of the bearing pressure plate, while ensuring that the pressure-bearing surface of the specimen is perpendicular to its forming surface, and the pressure is continuously and steadily increased until the test is completed. After each test, the maximum pressure value reached is recorded. Each ratio of the specimen was tested three times independently, and the average value was taken as the result. The calculation formula for compressive strength is as follows:

[0057]

[0058] Where: fc is the compressive strength of the specimen (MPa), F is the load when the specimen is destroyed (N), and A is the area of ​​the pressure-bearing surface of the specimen (mm2).

[0059] Finally, the test results are shown in Table 1:

[0060] Table 1. Performance index test results of embodiments and comparative examples

[0061]

[0062]

[0063] By comparing the data of Example 2 and Comparative Example 1 (wet method), it can be obtained that the pressed products prepared by the semi-dry method proposed in the present invention have significantly improved compressive strength compared to the cast products formed by the wet process, effectively overcoming the problem of low strength of wet forming.

[0064] By comparing the data of Example 2 and Comparative Example 2 (dry method), it can be obtained that: although the performance of the pressed products prepared by the semi-dry method of the present invention is not much different from that of the pressed products formed by the dry method, the steps of drying, grinding and adding water at the later stage are reduced, which effectively overcomes the shortcomings of the dry method, such as complex process and high energy consumption, and avoids the repeated process of dehydration followed by adding water.

[0065] By comparing the data of Example 2 with Comparative Examples 3 and 4, it can be seen that the anionic and cationic composite biopolymer curing agent used in the present invention has significantly improved compressive strength compared with the anionic or cationic biopolymer curing agent used alone. This shows that there is a positive synergistic effect between the anionic and cationic biopolymers, which can effectively enhance the mechanical properties of the material.

[0066] Comparing the data of Example 2 and Comparative Example 5, it can be seen that the microwave curing method used in the present invention shows a significant improvement in mechanical properties compared to traditional steam curing. This is mainly due to the strong penetration of the microwave source of a specific frequency, which allows the polymer powder inside the solidified body to fully dissolve with the water in the sand washing mud under the action of microwaves and evenly wrap the soil particles. As the water gradually evaporates, a network structure is formed, which further enhances the mechanical properties of the pressed product through the "bending mechanism" and "interweaving mechanism".

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0068] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a washed sand mud-based pressed product, characterized in that: The method comprises the following steps: S1. Semi-dry dehydration of sand washing mud to a moisture content of 15% to 20%; S2, mixing the semi-dry washed sand mud with biopolymer powder to obtain a premix, wherein the biopolymer powder includes cationic polymer powder and anionic polymer powder, the cationic polymer powder is any one of chitosan, cationic starch, cationic cellulose derivatives and polyquaternary ammonium salts, and the anionic polymer powder is any one of sodium alginate, anionic cellulose, collagen, pectin and gum arabic; S3, loading the premix into a mold and pressing it to obtain a mold base for a pressed product; S4. Activating the mold base of the pressed product by microwaves to obtain a washed sand mud-based pressed product.

2. The method for preparing a sand-washing mud-based pressed product according to claim 1, characterized in that: The sand washing mud accounts for 96% to 98% by weight, and the biopolymer accounts for 2% to 4% by weight.

3. The method for preparing a sand-washing mud-based pressed product according to claim 1 or 2, characterized in that: The mass ratio of the cationic polymer to the anionic polymer is in the range of (80-90):(10-20).

4. The method for preparing a sand-washing mud-based pressed product according to claim 1, characterized in that: The microwave activation includes preliminary microwave activation and deep microwave activation, wherein the time range of the preliminary microwave activation is 45min to 60min, the microwave frequency is 433MHz to 915MHz, and the time range of the deep microwave activation is 30min to 45min, the microwave frequency is 245MHz to 915MHz.

5. The method for preparing a sand-washing mud-based pressed product according to any one of claims 1 to 4, characterized in that: The molding pressure range of the premix compression molding in step S3 is 10MPa to 15MPa.

6. The method for preparing a sand-washing mud-based pressed product according to claim 1, characterized in that: The temperature range of the microwave activation is 50° C. to 80° C., and the power range of the microwave is 2 kW to 5 kW.

7. A sand-washing mud-based pressed product, characterized in that: A washed sand mud-based pressed product prepared by the method for preparing a washed sand mud-based pressed product according to any one of claims 1 to 6.

Citation Information

Cited By

  • Water-retaining aggregate with core-shell structure as well as preparation method and application of water-retaining aggregate

    CN121107731A